THE SELECTIVE ROLE OF PROFITABILITY IN THE RELATIONSHIP BETWEEN FINANCIAL RATIOS AND FINANCIAL DISTRESS OF COMPANY PROPERTY AND REAL ESTATE IN SOUTHEAST ASIA - Sukirno Sukirno; Nurul Hotimah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study examines the relationship between financial ratios and financial distress, positioning profitability as a moderating variable among property and real estate companies in Southeast Asia for the period 2012–2022. This study addresses two research gaps: the inconsistency of empirical findings on the influence of activity ratios, leverage, and liquidity on financial distress, and the limited evidence on whether profitability truly serves as a moderating mechanism in specific regional and sectoral contexts. The study uses a quantitative approach with secondary data in the form of annual reports, a purposive sampling technique, and results in 15 companies with 165 observations. The analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with the help of SPSS version 29. The results show that total asset turnover and current ratio have a significant positive effect on financial distress, while the debt-to-equity ratio has a significant negative effect. Simultaneously, all three financial ratios have a significant effect on financial distress. The most important finding of this study is that return on assets does not function as a universal moderator: profitability does not moderate the relationship between total asset turnover and debt-to-equity ratio on financial distress, but only moderates the relationship between the current ratio and financial distress. Thus, this study confirms that profitability has a selective, not generic, role in explaining financial distress, while expanding the understanding that the industry context and the character of the financial ratios tested largely determine the effectiveness of moderating variables.